2019
DOI: 10.1002/hbm.24585
|View full text |Cite
|
Sign up to set email alerts
|

Differential regional decline in dopamine receptor availability across adulthood: Linear and nonlinear effects of age

Abstract: Theories of adult brain development, based on neuropsychological test results and structural neuroimaging, suggest differential rates of age‐related change in function across cortical and subcortical sub‐regions. However, it remains unclear if these trends also extend to the aging dopamine system. Here we examined cross‐sectional adult age differences in estimates of D2‐like receptor binding potential across several cortical and subcortical brain regions using PET imaging and the radiotracer [18F]Fallypride in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 61 publications
5
35
1
Order By: Relevance
“…Given that our PET RAC assessment is on 18-32 year-olds, this may reflect the decline in receptors that follows a similar peri-adolescent peak observed in rodent models 9,11,15 . Further, similar to rodent models that find that NAcc DA receptor concentrations have either a less pronounced peak or a plateau during late adolescence 11,15 and recent findings from a human study of aging that showed a more shallow decrease in ventral striatum D2 receptors relative to caudate and putamen 33 , we also found a less pronounced association with age in the NAcc for RAC BP. While this result is compelling and aligns well with prior literature, it is important to note that spatial resolution is a limitation of PET imaging, particularly in small volumes such as NAcc, and limited spatial resolution may influence the diminished age-related reductions observed in NAcc RAC BP.…”
Section: Discussionsupporting
confidence: 88%
“…Given that our PET RAC assessment is on 18-32 year-olds, this may reflect the decline in receptors that follows a similar peri-adolescent peak observed in rodent models 9,11,15 . Further, similar to rodent models that find that NAcc DA receptor concentrations have either a less pronounced peak or a plateau during late adolescence 11,15 and recent findings from a human study of aging that showed a more shallow decrease in ventral striatum D2 receptors relative to caudate and putamen 33 , we also found a less pronounced association with age in the NAcc for RAC BP. While this result is compelling and aligns well with prior literature, it is important to note that spatial resolution is a limitation of PET imaging, particularly in small volumes such as NAcc, and limited spatial resolution may influence the diminished age-related reductions observed in NAcc RAC BP.…”
Section: Discussionsupporting
confidence: 88%
“…The [ 18 F]fallypride BP ND values in our low-risk participants (see unadjusted BP ND values in Supplementary Table 1) were similar to what have been previously found in a large sample of healthy volunteers [61]. However, the BP ND values in our adolescent sample overall were generally higher than what has been observed in middle-aged adults [61], consistent with DA 2 receptor expression declines with increased age [61,62].…”
Section: Discussionsupporting
confidence: 88%
“…The [ 18 F]fallypride BP ND values in our low-risk participants (see unadjusted BP ND values in Supplementary Table 1) were similar to what have been previously found in a large sample of healthy volunteers [61]. However, the BP ND values in our adolescent sample overall were generally higher than what has been observed in middle-aged adults [61], consistent with DA 2 receptor expression declines with increased age [61,62]. Of potentially greater importance, the [ 18 F]fallypride BP ND values in our high-risk participants and age-matched controls [61] were higher than what we have found in people with a current moderate to severe SUD [17,51], particularly in limbic and paralimbic regions (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, both the heterogeneous effects on distinct components of the DA system within individuals (e.g., presynaptic verses postsynaptic) as well as the substantial variability in DA function between individuals make it especially challenging to pinpoint the precise underlying root cause(s) for why and how dopaminergic mechanisms change with age (Berry, Jagust & Hsu, 2018a). Although numerous studies have reported a wide array of findings regarding changes in the DA system across adulthood (Bäckman, Lindenberger, Li, & Nyberg, 2010;Kaasinen et al, 2000;Kaasinen & Rinne, 2002;Volkow et al, 1998), as well as regional heterogeneity of age-related declines in DA binding potential (Seaman et al, 2019), a recent meta-analysis of the literature found healthy aging to be associated with reduced DA receptors and transporters, but no differences in DA synthesis capacity (Karrer, Josef, Mata, Morris, & Samanez-Larkin, 2017). Conversely, some have observed a positive association between elevated striatal DA synthesis capacity (caudate) and working memory in healthy older adults, which is also associated with increased fMRI BOLD signal in dorsolateral PFC during the delay period of a working memory task (Landau, Lal, O'Neil, Baker, & Jagust, 2009), whereas others have observed that higher DA synthesis capacity in older adults did not have a clear association with cognitive function (Berry et al, 2016;Braskie et al, 2008).…”
Section: Self-report Likert Ratings Reveal Access To Subjective Motivmentioning
confidence: 99%